The Application of Ripening Stimulant on Tamarillo (Chiphomandra betaceae) Packaged in Modified Atmosphere Packaging - Farhan Hawari Harahap; Elisa Julianti; Mimi Nurminah (Universitas Sumatera Utara, 2014)
Utilization of modified atmosphere packaging, can extend the shelf life of fruit. The research was done to evaluate the synergism between the delay of the ripening of tamarillo (Chiphomandra betaceae) through modified atmosphere and to be continued with the application of ripening stimulant material. The packaging treatment using a low density poliethylen plastic consists of an active modified atmosphere packaging with adsorben materials such as O2, CO2 and ethylene and also passive modified atmosphere packaging, then the packaged fruits were stored in two weeks. The application of ripening stimulant was done on the fruit that had been taken out from the packaging after 2 weeks storage. The materials of the ripening stimulant were ethepon 250 ppm, ethylene gas 250 ppm, acetylene gas 250 ppm and calcium carbide 0,3% (w/w). The results showed that there was a synergisme effect between the delay of a fruit ripening by a modified atmosphere packaging for two weeks storage that can be seen from the color score of a fruit skin, namely: 2 (yellowish green), and after treatment by the ripening stimulant, it was followed by a normal fruit ripening that was shown by a changing of skin colour to red and softening of the pulp. . Key words : modified atmosphere packaging, ripening stimulant, tamarillo